TRAINING THE VERNACULAR LENS HOW PROFESSIONAL DEVELOPMENT SHAPES PUBLIC HEALTH STORYTELLING IN HINDI NEWSROOMS OF UTTAR PRADESH - Dhar, Aarti; Singh, Preeti; Dahiya, Surbhi (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This paper is an exploration of the role of professional development programs in determining the quality, correctness, and cultural appropriateness of the PR-level narrative of the state of public health in Hindi newsrooms in Uttar Pradesh. The study is based on qualitative and mixed-method research designs, such as, semi-structured interviews, newsroom ethnography and content analysis as the research questions explore how the journalists understand, internalize and apply health-communication principles following the training. The paper maps the professional development eco-system which affects vernacular journalism; it includes capacity-building in-house, training programmes run by NGOs, external workshops and new forms of digital learning. Results indicate that systematic training has a tendency to enhance the sourcing habit, verification procedures and acquaintances with evidence-based designs among journalists especially in epidemic cover, sanitation, mother health, and vaccination campaigns. Also, due to training, narrative strategies are dramatically transformed: reporters become more open to clearer risk-communication strategies, more willing to explain complex health-related ideas with local metaphors, and more willing to include the solution-based frames most inclined to appeal to local audiences. The visual storytelling is also developed and journalists are more confident in using infographics, data about the district level, and images that are significant to the culture. Nevertheless, there is still a set of challenges that put the impact into check such as hierarchy in editorial control, uneven access to training and time constraints to do in-depth reporting.